Incidental findings in UK healthy volunteers screened for a COVID‐19 vaccine trial. Issue 2 (20th October 2021) - Hodgson, Susanne H.; Iveson, Poppy; Larwood, Jessica; Roche, Sophie; Morrison, Hazel; Cosgrove, Catherine; Galiza, Eva; Ikram, Sabina; Lemm, Nana‐Marie; Mehdipour, Savviz; Owens, Daniel; Pacurar, Mihaela; et al.
Abstract: The safety of novel therapeutics and vaccines are typically assessed in early phase clinical trials involving "healthy volunteers." Abnormalities in such individuals can be difficult to interpret and may indicate previously unrecognized medical conditions. The frequency of incidental findings (IFs) in healthy volunteers who attend for clinical trial screening is unclear. To assess this, we retrospectively analyzed data for 1838 "healthy volunteers" screened for enrolment in a UK multicenter, phase I/II severe acute respiratory syndrome‐coronavirus 2 (SARS‐COV‐2) vaccine trial. Participants were predominantly White (89.7%, 1640/1828) with a median age of 34 years (interquartile range [IQR] = 27–44). There were 27.7% of participants (510/1838) who had at least one IF detected. The likelihood of identifying evidence of a potential, new blood‐borne virus infection was low (1 in 238 participants) compared with identification of an elevated alanine transaminase (ALT; 1 in 17 participants). A large proportion of participants described social habits that could impact negatively on their health; 21% consumed alcohol in excess, 10% were current smokers, 11% described recreational drug use, and only 48% had body weight in the ideal range. Our data demonstrate that screening prior to enrollment in early phase clinical trials identifies a range of IFs, which should inform discussion during the consent process. Greater clarity is needed to ensure an appropriate balance is struck between early identification of medical problems and avoidance of exclusion of volunteers due to spurious or physiological abnormalities. Debate should inform the role of the trial physician in highlighting and advising about unhealthy social habits.